Konservasi Jenis Hiu Paus (Rhincodon typus) sebagai Ekowisata di Kawasan Kampung Kwatisore Distrik Yaur Kabupaten Nabire Provinsi Papua - Andarias Hamberi; Dwi Indah Widya Yanti; Lanny Karamoy (Lembaga Penelitian dan Pengabdian, Universitas Kristen Papua, 2022)
Whale shark (Rhincodon typus) conservation as ecotourism in the kwatisore Village area, Yaur District, Nabire Regency, Papua Province was carried out with the aim of knowing the types of Whale Shark (Rhincodon typus) conservation activities and the ecotourism potential of Kwatisore Village, Yaur District, Nabire Regency. From the results of research in Kwatisore Village, Yaur District, using the observation method and interview method, the results obtained were whale shark conservation activities, the potential for eco-tourism in Kwatisore village, and whale shark conservation involving various parties, the Cendrawasih Bay National Park Center, WWF-Indonesia. Conservation International, The Nature conservancy, Fisheries and maritime Service, Tourism, Youth Culture and Sports Office of Nabire Regency, conservation cadres and the people of Kwatisore village.